The Implication of Stem Cells in Direct Pulp Capping: Where Do We Stand? - Madiha Khan; Zainab Haji; Robia Ghafoor (Journal of the Pakistan Medical Association, 2023)
Direct pulp capping has been established as a more conservative alternative to root canal therapy, especially in case of an iatrogenic or traumatic exposure of the dental pulp. However, recent literature focuses on regeneration therapies to develop a physiological dentin barrier. The process of tissue regeneration through stem cell therapy involves a complex interaction between stem cells, growth factors and scaffolds known as the ‘tissue engineering triad’. Recent advancements in stem cell therapy focus on the re programming of stem cells, development of scaffolds and enhancement of the regenerative potential of these stem cells, using appropriate growth factors and transfer media. This article provides a summary of the current evidence regarding the use of stem cell therapy in direct pulp capping. The sources of stem cells, types of scaffolds and growth factors have been described in detail along with the limitations and future prospects. Continued...